Detection of spatial and temporal spread of Mycobacterium avium subsp. paratuberculosis in the environment of a cattle farm through bio-aerosols - Eisenberg, S.W.F.; Nielen, M.; Santema, W.; Houwers, D.J.; Heederik, D.; Koets, A.P. (Veterinary microbiology, 2010)
Environmental samples were collected to investigate the spatial and temporal spread of Mycobacterium avium subsp. paratuberculosis (MAP) in a dairy cattle barn before and after the introduction of two groups of MAP-shedding animals. Samples collected off the floor of the barn reflected the moment of sampling whereas samples collected by microfiber wipes at a minimal of 3 m height contained the accumulated settled dust over a 3-week period. Samples were analysed by IS 900 qPCR for the presence of MAP DNA and by culture for viable MAP bacteria. MAP DNA was detected in a large number of sites both before and after introduction cattle. MAP DNA was detected inside the barn in floor and dust samples from cubicles and slatted floors and in settled dust samples located above the slatted floors and in the ventilation ridge opening. Outside the barn MAP DNA was detected by PCR in samples reflecting the walking path of the farmer despite hygiene measures. No viable MAP was detected before the introduction of shedder cattle. Three weeks later viable MAP was found inside the barn at 7/49 locations but not outside. Fifteen weeks later viable MAP was also detected in environmental samples outside the barn. In conclusion, introduction of MAP shedding cattle lead to widespread contamination of the internal and external environment of a dairy barn, including the presence of viable MAP in settled dust particles suggesting potential transmission of MAP infection through bio-aerosols.